LOGOTHERAPY ON QUALITY OF LIFE IN CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMDOIALYSIS: A LITERATURE REVIEW - Putro, Dimas Utomo Hanggoro; Handayani, Buntar; Wahyuningsih, Sri Atun (Nurse and Health: Jurnal Keperawatan, 2024)
Background: Chronic kidney disease is a chronic disease that causes death rates to always increase. Chronic kidney disease patients require hemodialysis therapy. Hemodialysis therapy will have an impact on the quality of life of chronic kidney disease patients. Objective: This literature review aims to identify the effect of logotherapy on the quality of life of chronic kidney disease patients undergoing hemodialysis. Design: This research design is a literature review. Data Sources: Search for articles using three journal databases, namely Google Scholar, PubMed, and Science Direct. Review Methods: Used PRISMA flow diagram to find a total of 6 articles that met the inclusion criteria reviewed. Results: Keywords in English "Chronic Kidney Disease Patient AND Logotherapy AND Quality Of Life AND Hemodialysis ". Key words in Indonesian "Gagal Ginjal Kronik AND Logoterapi AND Kualitas Hidup AND Hemodialisis”. Inclusion criteria include full text articles from 2015-2024 in Indonesian or English published from national or international journals. Article types are quasi-experimental, semi-experimental and case studies. Six articles met the inclusion criteria. Logotherapy is useful for gaining behavioral values such as accepting with full fortitude, patience, courage to face forms of suffering, and giving the spirit to make life meaningful Conclusion: Logotherapy is a type of psychotherapy to improve the quality of life through discovering and achieving the meaning of life. Logotherapy It is useful for gaining behavioral values such as accepting with full fortitude, patience, courage to face forms of suffering, and giving the spirit to make life meaningful